Bahasa Indonesia: english - Prada, Diego Meihestu; Martinius, Martinius (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2020)
Brown planthopper or BPH (Nilaparvata lugens Stal 1854, Hemiptera: Delphacidae) is one of the main pests in rice plant that destructive by sucking on saps. Difference in rice varieties is predicted to affect the biology and demographic statistics of BPH. The study aimed to determine the biology and demographic statistics of BPH on Cisokan and Kahayan varieties. BPH biology was observed from 10 pairs of BPH per each variety, while demographic statistic was observed from cohort of egg produced by 10 pairs of BPH. The parameters were number of individuals per stadia, life time and life span. Data were processed to obtain biology, survival curve and demographic statistic. The results showed that differences in varieties affected the life time and the number of individuals produced by BPH. The life time of the eggs, 1st – 4th instar of nymphs on Cisokan were shorter than Kahayan, but the 5th instar of nymphs and adult on Cisokan were longer than Kahayan. The number of eggs, nymphs and adults on Cisokan were higher than Kahayan. Both the survival curves on Cisokan and Kahayan were included as type 1. Keywords: Biology, brown planthopper, Cisokan variety, Kahayan variety